Optical properties and thermal stability of La1−xSrxCoO3−δ (0.2 ⩽ x ⩽ 0.8) ceramics. (1st November 2016) - Fang, Zhenggang; Lu, Chunhua; Ma, Delin; Wei, Ling; Li, Peiwen; Ni, Yaru; Tao, Shunyan; Xu, Zhongzi
Highlights: The optical properties of La1 − x Sr x CoO3 − δ (0.2 ⩽ x ⩽ 0.8) ceramics were studied. The investigated samples showed low thermal emittance at high temperatures. La0.5 Sr0.5 CoO3 − δ solar absorber was thermally stable in air up to 800 °C for 10 cycles (90 h). Abstract: Perovskite-type La1 − x Sr x CoO3 − δ (0.2 ⩽ x ⩽ 0.8) ceramics were prepared by tape casting and solid state reaction method. The room temperature optical properties of these samples were studied in detail. The temperature dependent emittance measurements and high-temperature durability tests were carried out. Results showed that these materials exhibited low reflectance at the solar spectrum wavelengths and high reflectance in the infrared region, with an optimal spectral selectivity of 3.2. The investigated samples showed low thermal emittance at high temperatures. More importantly, the sample was highly stable in air at 800 °C, as the performance criterion value was lower than 0.05 after 10 cycles (90 h) heat treatment. Our results demonstrate that the La1 − x Sr x CoO3 − δ ceramics have the potential to emerge as high temperature (∼800 °C) solar absorbers for the future solar power systems.